Peran Promosi Penjualan pada Usaha Omah Batik Srikandi dan Edukriya Keluruhan Jatisari Kecamatan Mijen Kota Semarang - Muchayatin Muchayatin; Sulistiyani Sulistiyani; Ribut Musprihadi (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
This community service aims to improve the marketing and sales promotion capabilities of batik MSMEs, especially Omah Batik Srikandi and Edukriya in Jatisari Village, Mijen District, Semarang City. The approach includes training and mentoring by providing knowledge and skills of effective sales promotion strategies in marketing batik. Its activities intend to increase batik promotion and sales through the development of innovative sales promotion strategies, such as discounts, gifts, and others. Through this approach, it is hoped that batik MSMEs can increase sales, expand market reach, and support the preservation of batik cultural heritage in Semarang City. Increasing the competitiveness of batik MSMEs is also expected to be achieved, thus having a positive impact on the local and national economy.